18F-fluorodeoxyglucose positron emission tomography and the risk of subsequent aortic complications in giant-cell arteritis: A multicenter cohort of 130 patients. Issue 26 (June 2016) - de Boysson, Hubert; Liozon, Eric; Lambert, Marc; Parienti, Jean-Jacques; Artigues, Nicolas; Geffray, Loïk; Boutemy, Jonathan; Ollivier, Yann; Maigné, Gwénola; Ly, Kim; Huglo, Damien; Hachulla, Eric; et al.
Abstract : Abstract: Previous studies reported a 2- to 17-fold higher risk of aortic complications (dilation or dissection) in patients with giant-cell arteritis (GCA). We aimed to determine whether or not GCA patients with large-vessel involvement demonstrated by positron emission tomography with 18 F-fluorodeoxyglucose combined with computed tomography (FDG-PET/CT) have a higher risk of aortic complications. We conducted a retrospective multicenter study between 1995 and 2014. Patients were included if they fulfilled at least 3 American College of Rheumatology criteria for GCA, or 2 criteria associated with extratemporal biopsy-proven giant-cell vasculitis; they underwent at least 1 FDG-PET/CT scan at diagnosis or during follow-up; and the morphology of the aorta was assessed by medical imaging at diagnosis. Patients with an aortic complication at the time of diagnosis were excluded. Of the 130 patients included [85 women (65%), median age 70 (50–86)], GCA was biopsy proven in 77 (59%). FDG-PET/CT was performed at diagnosis in 63 (48%) patients and during the follow-up period in the 67 (52%) remaining patients. FDG-PET/CT was positive in 38/63 (60%) patients at diagnosis and in 31/67 (46%) patients when performed during follow-up ( P = NS). One hundred four patients (80%) underwent at least 1 morphological assessment of the aorta during follow-up. Nine (9%) patients developed aortic complications (dilation in all and dissection in 1) at a median time of 33 (6–129) months after diagnosis. All of them displayed large-vessel inflammation on previous FDG-PET/CT. A positive FDG-PET/CT was significantly associated with a higher risk of aortic complications ( P = 0.004). In our study, a positive FDG-PET/CT was associated with an increased risk of aortic complications at 5 years.